Materiais táteis e a obra de João Sebastião da Costa - Davies, Silvia Mara (2017)
The present study, enrolled in the research line "Contemporary Poetics", of the Postgraduate Program in Contemporary Culture Studies, had as objective to investigate the techniques and theoretical foundations that guide the construction of tactile materials and mediation resources used in technical expo mediation graphics aimed at visually impaired people in museums. To make the paintings accessible to the visually impaired, museums use a variety of mediation resources, such as the transposition of works of art into tactile materials, the provision of works to the touch, embossing, representational texture, audiodescription, Braille information and enlarged letters, olfactory resources and attendance by the mediator. The research investigated the techniques and theoretical foundations having as main theoretical framework Tojal (1999, 2007, 2013), Almeida (2010), Amiralian (1997), Valente (2010), to realize the transformation of two-dimensional work, made to be seen, in resources adapted to People with visual impairment. For that, the work of artist João Sebastião Francisco da Costa (1949-2016) was transposed into tactile materials. The present study was carried out in two moments: The first one corresponds to the exploratory research, in which the diagnostic analysis of the accessibility was done in three museums of Cuiabá-MT. The second stage refers to experimental research, whose methodology covered empirical procedures in the elaboration of tactile material and included several research techniques such as interviews, bibliographical research, and case study. With regard to the empirical research involving the tactile materials, a work of the artist belonging to the collection of the "Museum of Art and Popular Culture" of the Federal University of Mato Grosso, Cuiabá Campus was selected.The experimental phase of the research was developed in several stages : In the first stage, bibliographical studies were carried out and the techniques of transposing images for tactile materials were carried out. The second stage involved the preparation of the tactile materials and the elaboration of the mediation project. The third stage corresponded to the organization of the exhibition in the museum, and a course project was developed for the visually impaired, with students from the Instituto dos Cegos de Mato Grosso (ICEMAT) as participants in the research. The final stage corresponded to the application of mediation resources through the mediation project in the museum space. instruments used for data collection were recordings of the reports and obser- during the assessment of mediation resources. It was observed during the assessments that the participants had many difficulties in identifying the contoured drawings in reliefs on the tactile plates. The sculptures enabled tactile exploration in all dimensions and represented an important accessibility strategy. Objects with original material properties such as odor, texture, shape and dimensions were quickly perceived. Through the accomplishment of this research and the data analysis, it is possible to verify the relevance of the use of mediation resources as a strategy of aesthetic accessibility. The application of mediation resources in the museum space of the MACP has brought important data that can help researchers to develop mediation projects that aim to enable aesthetic access of visual works through tactile materials to people with visual impairments.